Apatinib combined with PD-1 antibody for third-line or later treatment of advanced gastric cancer - Cui, Qingli; Mao, Yuefeng; Wu, Daoyuan; Hu, Yanhui; Ma, Dongyang; Zhang, LiHan; Liu, Huaimin (Frontiers in Oncology, 2022)
Background: Both apatinib and programmed death 1 (PD-1) monoclonal antibody (mAb) monotherapy have been licensed in China for the third-line treatment of advanced gastric cancer (AGC). However, whether the combination could improve the prognosis of patients with AGC after second-line treatment has not been evaluated. Methods: We retrospectively screened 892 patients with AGC who received third-line or later treatment from June 2016 to July 2021 at the Affiliated Cancer Hospital of Zhengzhou University and second People’s Hospital of Pingdingshan. 166 patients who received apatinib plus PD-1 mAb, apatinib, or PD-1 mAb were included. Based on medical records and follow-up data, we analyzed the efficacy and safety of these three treatment options. Results: Patients received apatinib plus PD-1 mAb (n=49), apatinib monotherapy (n=63), or PD-1 mAb monotherapy (n=54). Apatinib plus PD-1 mAb showed significantly longer progression-free survival (PFS) and overall surivival (OS) compared with the apatinib monotherapy (PFS: 5.5 months versus 3.0 months; p=0.002; OS: 10 months versus 7.6 months; p=0.011) or PD-1 mAb monotherapy (PFS: 5.5 months versus 2.3 months; p=0.017; OS: 10 months versus 6.5 months; p=0.004). Apatinib plus PD-1 mAb showed higher ORR and DCR than the apatinib and PD-1 mAb monotherapy (ORR: 34.7% versus 6.3% versus 9.3%; p=0.001; DCR: 75.5% versus 44.4% versus 40.7%; p=0.001). Further subgroup analysis for PFS and OS shown consistent efficacy in most subgroups with apatinib plus PD-1 mAb versus apatinib monotherapy or PD-1 mAb monotherapy. Multivariate analyses suggested that apatinib plus PD-1 mAb was significantly associated with better PFS and OS. Most of the treatment-related toxicities were mild and tolerable. Conclusion: Compared with the monotherapy of either apatinib or PD-1 mAb, apatinib plus PD-1 mAb treatment yielded longer PFS and OS, and achieved significant higher ORR and DCR.